Results of a phase 1 multicentre investigation of dexmedetomidine bolus and infusion in corrective infant cardiac surgery - Zuppa, Athena F.; Nicolson, Susan C.; Wilder, Nicole S.; Ibla, Juan C.; Gottlieb, Erin A.; Burns, Kristin M.; Stylianou, Mario; Trachtenberg, Felicia; Ni, Hua; Skeen, Tera H.; Andropoulos, Dean B. (British journal of anaesthesia : BJA, 2019)
Dexmedetomidine (DEX) is increasingly used intraoperatively in infants undergoing cardiac surgery. This phase 1 multicentre study sought to: (i) determine the safety of DEX for cardiac surgery with cardiopulmonary bypass; (ii) determine the pharmacokinetics (PK) of DEX; (iii) create a PK model and dosing for steady-state DEX plasma levels; and (iv) validate the PK model and dosing. We included 122 neonates and infants (0–180 days) with D-transposition of the great arteries, ventricular septal defect, or tetralogy of Fallot. Dose escalation was used to generate NONMEM® PK modelling, and then validation was performed to achieve low (200–300 pg ml−1), medium (400–500 pg ml−1), and high (600–700 pg ml−1) DEX plasma concentrations. Five of 122 subjects had adverse safety outcomes (4.1%; 95% confidence interval [CI], 1.8–9.2%). Two had junctional rhythm, two had second-/third-degree atrioventricular block, and one had hypotension. Clearance (CL) immediately postoperative and CL on CPB were reduced by approximately 50% and 95%, respectively, compared with pre-CPB CL. DEX clearance after CPB was 1240 ml min−1 70 kg−1. Age at 50% maximum clearance was approximately 2 days, and that at 90% maximum clearance was 18 days. Overall, 96.1% of measured DEX concentrations fell within the 5th–95th percentile prediction intervals in the PK model validation. Dosing strategies are recommended for steady-state DEX plasma levels ranging from 200 to 1000 pg ml−1. When used with a careful dosing strategy, DEX results in low incidence and severity of adverse safety events in infants undergoing cardiac surgery with cardiopulmonary bypass. This validated PK model should assist clinicians in selecting appropriate dosing. The results of this phase 1 trial provide preliminary data for a phase 3 trial of DEX neuroprotection. NCT01915277.